Pendampingan E-LKPD Inovatif Berbasis Platform Live Worksheet Model Project Based Learning bagi Mahasiswa PGSD Unwidha - Sri Rahayu; Elisabeth Aska; Sri Utami; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2024)
Learning problems found at Unwidha as a partner in this service program include (1) students have not been able to create digital-based E-LKPD with applications, (2) students have not been able to create LKPD according to the syntax of the learning model. The best solution to this main problem is a training and assistance program for creating digital-based E-LKPD using the Live Worksheet application. The general aim of this program is to improve the digital literacy skills of PGSD Unwidha students. The specific objectives are (1) to provide training in making E-LKPD with the Live Worksheet application and (2) to provide assistance in making E-LKPD with the Live Worksheet application. The target of this activity is PGSD Unwidha Klaten students in semesters 3 and 5. The methods applied are workshops and mentoring. The workshop was delivered offline with material that focused on LKPD, E-LKPD, and the use of Live Worksheets in preparing E-LKPD. The results of this activity are skills in compiling E-LKPD by PGSD Unwidha students. This e-LKPD can then be implemented in the following semester.